Acute fatty liver of pregnancy and it’s anesthetic implications (Indian Journal of Case Reports, 2020)
Acute fatty liver of pregnancy (AFLP) is a rare and potentially fatal disorder that usually manifests in the third trimester or even sometimes after delivery. Anesthesiologists are an important part of the multidisciplinary team involved in the management of such patients during their perioperative care and as well as in the intensive care unit (ICU). AFLP usually manifests with deranged liver and renal function tests and episodes of hypoglycemia. The diagnosis is typically clinical. Prompt delivery and supportive care in ICU are the cornerstone of treatment. We, hereby, describe the successful management of the patient with postpartum AFLP in ICU.